2022
DOI: 10.1039/d1ta09864k
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube supported manganese selenide as a highly active bifunctional OER and ORR electrocatalyst

Abstract: Transition metal selenides have attracted intensive interest as cost-effective electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) because of the continuous thrust in sustainable energy conversion. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 68 publications
3
62
0
Order By: Relevance
“…Direct methanol fuel cells (DMFCs) are considered to be promising sources of vehicle power to solve the need for sustainable energy; however, the oxygen reduction reaction (ORR), a key half-reaction of DMFCs, severely hinders their commercial application because of the extremely slow kinetics rate. [1][2][3][4][5] Therefore, it is particularly urgent to develop or design high-performance ORR catalysts. Although Pt-based nanomaterials are widely employed as the most advanced ORR catalysts, unfavorable factors, such as high cost, scarcity, unsatisfactory durability, and poor methanol-resistance, have greatly hindered their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Direct methanol fuel cells (DMFCs) are considered to be promising sources of vehicle power to solve the need for sustainable energy; however, the oxygen reduction reaction (ORR), a key half-reaction of DMFCs, severely hinders their commercial application because of the extremely slow kinetics rate. [1][2][3][4][5] Therefore, it is particularly urgent to develop or design high-performance ORR catalysts. Although Pt-based nanomaterials are widely employed as the most advanced ORR catalysts, unfavorable factors, such as high cost, scarcity, unsatisfactory durability, and poor methanol-resistance, have greatly hindered their large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…8 Previous reports demonstrated that SACs have broad prospects in decreasing the catalyst cost, increasing the catalytic performance, and serving as model catalysts for specic reactions. 2,9 First, the SACs with uniformly dispersed metal active sites possess the merits of extremely high atomic utilization and low metal loading; second, a clear reaction mechanism can be derived for specic reactions; nally, the unique electronic structure of SACs and the unsaturated coordination environment of the active centers are conducive to improving the desorption capacity of reaction intermediates, thereby increasing the catalytic activity. 2,10 No doubt, the strong interaction between the support and metal plays an important role in the separation, dispersion, and stabilization of individual atoms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from enhanced catalytic activity, these CoTe nanostructures also showed high faradaic efficiency, and longterm functional stability. Also, because of the extensive stoichiometry alterations that are possible in metal-rich chalcogenides, these materials are highly efficient, inexpensive, and robust electrocatalysts for a variety of electrochemical sensors, energy conversion, and storage applications [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%